MiRNA-146a/AKT/β-Catenin Activation Regulates Cancer Stem Cell Phenotype in Oral Squamous Cell Carcinoma by Targeting CD24 - Ghuwalewala, Sangeeta; Ghatak, Dishari; Das, Sumit; Roy, Stuti; Das, Pijush; Butti, Ramesh; Gorain, Mahadeo; Nath, Somsubhra; Kundu, Gopal C.; Roychoudhury, Susanta (Frontiers in Oncology, 2021)
CD44highCD24low population has been previously reported as cancer stem cells (CSCs) in Oral Squamous Cell Carcinoma (OSCC). Increasing evidence suggests potential involvement of microRNA (miRNA) network in modulation of CSC properties. MiRNAs have thus emerged as crucial players in tumor development and maintenance. However, their role in maintenance of OSCC stem cells remains unclear. Here we report an elevated expression of miR-146a in the CD44highCD24low population within OSCC cells and primary HNSCC tumors. Moreover, over-expression of miR-146a results in enhanced stemness phenotype by augmenting the CD44highCD24low population. We demonstrate that miR-146a stabilizes β-catenin with concomitant loss of E-cadherin and CD24. Interestingly, CD24 is identified as a novel functional target of miR-146a and ectopic expression of CD24 abrogates miR-146a driven potential CSC phenotype. Mechanistic analysis reveals that higher CD24 levels inhibit AKT phosphorylation leading to β-catenin degradation. Using stably expressing miR-146a/CD24 OSCC cell lines, we also validate that the miR-146a/CD24/AKT loop significantly alters tumorigenic ability in vivo. Furthermore, we confirmed that β-catenin trans-activates miR-146a, thereby forming a positive feedback loop contributing to stem cell maintenance. Collectively, our study demonstrates that miR-146a regulates CSCs in OSCC through CD24-AKT-β-catenin axis.